The interactive roles of lexical knowledge and reading strategies on reading comprehension performance among EOP learners at UiTM Terengganu - Zuriyani Md. Yasin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The current study is an investigation into the interactive roles of lexical knowledge and reading strategies on reading comprehension performance of EOP learners at UiTM Terengganu. It determines whether the lexical knowledge or the reading strategies contribute to L2 reading comprehension. It examines whether there is a relationship among the three main variables. In order to accomplish this, the Survey of Reading Strategy (SORS) (Mokhtari & Sheorey, 2002), the Vocabulary Levels Test (Smith, 2000), a writing test and a reading comprehension test were administered to 70 fourth-semester students from the Public Administration course. Descriptive statistics were used to describe the respondents' performance on these three tests and their reported reading strategies used as well as to assess the relationship between the three main variables of this study. As a whole, the respondents reported using most of the reading strategies with high and moderate frequencies. They also reported that they frequently use the global strategies. Apart from that, it is found that, the word mastery level of the EOP students of UiTM Terengganu is only 2,000 word families, which is far below the minimum level required for the tertiary level of education. There is no correlation found between the reading strategies used and the reading comprehension achievement of the respondents. On the other hand, a statistically significant relationship (r=.74, p<0.01) was found between the participants' vocabulary size and reading comprehension performance. The study concludes with some theoretical and pedagogical implications as well as recommendations for further research.